Design and development of an intelligent net-zero energy building for remote, harsh weather locations - Salami, Momoh Jimoh Emiyoka ([s.n], 2012)
It is generally reckoned that the building industry consumes considerable quantities of energy and material resources [1]. Via energy auditing conducted, it has been observed that the library building in some higher institution consumes tremendous energy among all buildings in the institution. Through energy auditing also, the inefficiency in utilizing the existing cooling and lighting systems have also being realized. Thus in order to overcome these problems, the existing systems can be modified using the concept of artificial intelligent building. The ultimate aim of this work is to achieve energy efficiency in building without neglecting the comfort of the user. The intelligent cooling and lighting systems can be controlled via selected sensors such as temperature sensor and infrared motion sensor that are integrated with the main controller. Fuzzy logic (FL) control technique has also been implemented in this work .The parameters involved are light intensity, the number of occupants and the room temperature. Measurements of these parameters were done by implementing suitable sensors according to the condition. The output of the system will then supply the sufficient illuminance level and the cooling rate for comfort of the occupants.